51.3k views
4 votes
Answer ,how to do it.

Answer ,how to do it.-example-1

1 Answer

3 votes

Answer:

The system has two solutions:

x₁ = 5 ⇒ y₁ = -10

x₂ = -2 ⇒ y₂ = 11

Explanation:

Let's solve the system of equations, this way:

y = -3x + 5

y = x ² - 6x - 5

Replacing y in the 2nd equation:

y = x ² - 6x - 5

-3x + 5 = x ² - 6x - 5

x ² - 3x - 10 = 0

Solving for x, using the quadratic formula:

(3 +/- √(9 -4 * 1 * -10))/2 * 1

(3 +/- √9 + 40)/2

(3 +/- √49)/2

(3 +/- 7)/2

x₁ = 10/2 = 5

x₂ = -4/2 = -2

x₁ = 5 ⇒ y₁ = -10

x₂ = -2 ⇒ y₂ = 11

As we can see the system has two different solutions

User Mhawke
by
5.0k points